EXPLORING TERTIARY STUDENTS’ CONCEPTION OF HEAT AND TEMPERATURE - Tanahoung, Choksin (วารสารวิชาการศึกษาศาสตร์ ศรีนครินทรวิโรฒ, 2017)
ABSTRACT This study employs the survey, the Heat and Temperature Conceptual Evaluation (HTCE), to study the understanding of thermal physics of a group of some 200 introductory physics students at the Ubon Ratchathani University. The classes was administered the HTCE survey for pre-instruction. The overall objective of the study was to determine if the HTCE survey can reliably gauge students’ conception. The pre-test scores and gender were considered as possible influences on student responses to the survey. We find that the HTCE survey can reliably gauge students’ conception and the basic conceptual areas of specific heat capacity and change of phase were particularly difficult for the students. There is a statistically significant difference between females and males in the pre-test mean score. Keywords : Heat and Temperature Conceptual Evaluation (HTCE) survey, Tertiary students’ conception